Sistem Hambatan Berlapis Digitalisasi UMKM Kuliner: Studi Kualitatif Berbasis Kerangka TOE - Dafitri, Rahma; Daryani, Dian (Politeknik Negeri Bali, 2025)
Digital transformation barriers in culinary micro, small, and medium enterprises (MSMEs) form a layered barrier system that mutually reinforces and hinders optimization. This qualitative exploratory study involving 10 culinary MSMEs in Bandung identifies five main dimensions of barriers with 42 sub-categories analyzed using NVIVO. Digital literacy emerges as the dominant barrier, followed by technical, financial, operational, and external barriers. The study reveals three new theoretical findings: digital financial literacy as an overlooked dimension, time constraints creating repetitive cycles, and optimization paradox showing the phenomenon of